Madurese Women and the Politics of Marriage: A concept of Marriage in the Globalization Era - Miftahur Roifah (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2021)
Globalization has contributed to the intensification of worldwide social relations that continuously increases the interconnectedness of people from diverse cultures. Its implication creates possibilities in spreading new or certain ideas through accessible telecommunication and the internet. It is undeniable that Madura is also affected by globalization particularly its cultural practices. Madurese people have frequently been confronted with a problematic phenomenon in their marriage tradition because arranged marriage and early marriage are still commonly practiced and have been passed down over generations for a long time. Both of the practices give unfair treatment to women since they violate their autonomy and independence. As globalization opens access to a new perspective of life, as people can experience another culture by traveling or connected through the internet, it provides a huge influence on the way people think, reacts, and responds to their own culture or tradition. In connection with this phenomenon, this study is going to elucidate how young Madurese women who have been exposed to the use of media and the internet conceptualize their marriage ideas, whether they still follow the old tradition or they have constructed a new concept of marriage. By applying a qualitative method, this study will conduct an interview and distribute a questionnaire to young Madurese women studying at the University of Trunojoyo Madura. The results indicate that globalization to some extent constructs the new perception of marriage for young Madurese women and builds a variety of interpretations based on what and how they connect themselves with the world outside their community.